An Enquiry into the Contributions of Microfinance Institutions Towards the Development of Small Scale Business in Nigeria - Isola, Lawal Adedoyin; Taiwo, Omoluabi Ehis; Victor, Ahmed; Leke, Babalola Kehinde (International Journal of Business, Economics and Management, 2014)
This paper examined the impact of Microfinance Institutions’ policies on the growth and development of Small Scale Business in Nigeria for the period 2005 to 2012. Nine (9) Microfinance Institutions and one hundred and fifty five (155) of their clients were interviewed. Records from the period shows that there is an increase in the numbers of savings and loans made by the Micro Finance Institutions, this signifies a rise in the need for Microfinance Institutions services in the economy. The study adopts the use of Multiple Regression Analysis to regress the relationship between the dependent variable and independent variables. We also employed the use of Analysis of Variance to determine the strength of the Regression Analysis. The OLS result suggests existence of positive relationship between both the dependent and independent relationship. Our findings suggested that macroeconomic policy should be designed in such a way that will encourage the survival of Microfinance Institutions and attracts low income – informal sector which in turn leads to increase in productivity and employment generation.